High-temperature oxygen nonstoichiometry and electrical conductivity of layered Ln2–xSrxNiO4–δ (Ln – La, Pr, Nd; х = 1.0 –1.6) nickelates - Kravchenko, Ekaterina S.; Zakharchuk, Kiryl V.; Pankov, Vladimir V.; Yaremchenko, Aleksey A. (Journal of the Belarusian State University. Chemistry, 2017)
High-temperature oxygen nonstoichiometry and electrical conductivity of Ln2 – xSrxNiO4 – δ (Ln – La, Pr, Nd; х = 1.0–1.6) nickelates were evaluated for potential application as oxygen electrodes of solid oxide fuel cells. In air, all studied nickelates were found to maintain tetragonal K2NiF4-type structure up to 1000 °С and to demonstrate oxygen deficiency above 500 °С. Oxygen nonstoichiometry increases with temperature and with strontium content in A sublattice. Ln2 – xSrxNiO4 – δ nickelates possess p-type metallic-like electrical conductivity under oxidizing atmosphere at 500 –1000 °С. In each series, the highest conductivity (260–400 S ⋅ cm–1, depending on rare-earth element) was observed for the composition with x = 1.2. Neodymium-containing nickelates demonstrate highest concentration of oxygen vacancies in the studied composition range.